2014
DOI: 10.3171/2014.2.jns132197
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of erythropoietin pretreatment in a rodent model of transient middle cerebral artery occlusion

Abstract: Object There is an unmet clinical need to develop neuroprotective agents for neurosurgical and endovascular procedures that require transient cerebral artery occlusion. The aim in this study was to explore the effects of a single dose of recombinant human erythropoietin (rhEPO) before middle cerebral artery (MCA) occlusion in a focal cerebral ischemia/reperfusion model. Methods Twenty-eight adult male Wistar rats were subjected to right MCA occlusion via the intraluminal thread technique for 60 minutes under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
3
16
1
Order By: Relevance
“…For gelatin zymography and Western blot analysis, the same animals were perfused via the ascending aorta with phosphate buffer saline solution, pH 7.4 (PBS). Brains were quickly removed, snap-frozen, and cryopreserved at −80°C for at least 24 h. Protein extracts were obtained by lysing the brain tissue with radioimmunoprecipitation assay (RIPA) buffer (Tris Buffer 1 M pH 8.0, EDTA 0.5 M pH 8.0, NaCl 5 M, 10% NP-40, 50% glycerol, 10% SDS) [ 53 ]. For cryo-histological analysis, B6 CX3CR1 gfp/+ animals were perfused with 4% PFA in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For gelatin zymography and Western blot analysis, the same animals were perfused via the ascending aorta with phosphate buffer saline solution, pH 7.4 (PBS). Brains were quickly removed, snap-frozen, and cryopreserved at −80°C for at least 24 h. Protein extracts were obtained by lysing the brain tissue with radioimmunoprecipitation assay (RIPA) buffer (Tris Buffer 1 M pH 8.0, EDTA 0.5 M pH 8.0, NaCl 5 M, 10% NP-40, 50% glycerol, 10% SDS) [ 53 ]. For cryo-histological analysis, B6 CX3CR1 gfp/+ animals were perfused with 4% PFA in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described [ 53 ] with minor alterations. Briefly, 100 μg of protein from tissue extracts were separated on a 12% SDS-PAGE gel.…”
Section: Methodsmentioning
confidence: 99%
“…Erythropoietin reduces inflammation by decreasing inflammatory cytokines, by attenuating reactivation astrocytosis and microglia activation and by inhibiting immune cells recruitment into the injured area ( 5 , 13 ). Although several in-vivo studies have shown an anti-inflammatory effect of erythropoietin, the affirmation of its in-vitro effect is controversial ( 4 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A small burr hole was drilled 1 mm posterior to bregma and 0.5 mm lateral to midline, and the micro-Doppler probe was positioned above the dura mater in a holder glued to the bone. LDF was monitored continuously and recorded at 15 min before ICH induction and at 15-min intervals thereafter until 3 h after injury [60,61]. …”
Section: Methodsmentioning
confidence: 99%